MUSYKILAH TA’LIMIYAH AL-LUGHAH AL-‘ARABIYAH BI JAMI’AH MAULANA MALIK IBRAHIM MALANG WA AL-HULUL AL-MUQTARAHAH LAHA - Bahruddin, Uril Bahruddin (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2017)
The State Islamic University (UIN) of Maulana Malik Ibrahim Malang is one of State Islamic University in Indonesia have been successfully developed Arabic. Since 1997 UIN Malang has started to require all new students to study Arabic intensively in an institution called Arabic Intensive Program (PKPBA) for a full first year. In the 20th of his age, with all the achievements and accomplishments that have been reached, the Arabic Intensive Program must be improved and developed. This article discusses about problems that faced in developing Arabic, at the same time look for ways to improve the next process of learning Arabic. From the analysis this article found that there are number of problems in Arabic development, including lecturer, student, textbook and management. After all, this article offered some solutions to solve the problem, (1) the lecturer should improve pedagogical quality through training, workshop and study, (2) always motivate student to learn Arabic, (3) Arabic Intensive Program need textbook that relevant to need of students, and (4) Arabic Intensive Program should make restoration and improvement in management.